Pfg NMR studies of lateral diffusion in oriented lipid bilayers. Issue 4 (2005) - Orädd Orädd, Greger Greger; Lindblom Lindblom, Göran Göran
Abstract : The pfg-NMR diffusion technique is proposed to have an appreciable potential for future biophysical investigations in the field of membrane biology. Topics like transport of molecules both across and in the plane of the membrane can be successfully studied, as well as the formation of lipid domains and their intrinsic dynamics can be scrutinized. This short review will introduce the fundamental aspects of orientation dependent NMR interactions and the technique of macroscopically oriented bilayers for eliminating the unwanted effects of those interactions. The pfg-NMR technique will be briefly introduced and finally, some recent results illustrating the potential of the method are presented.